Cytochrome c -peroxidase modulates ROS homeostasis to regulate the sexual mating of Sporisorium scitamineum - Cai, Enping; Jia, Huan; Feng, Ruqing; Zheng, Wenqiang; Li, Lei; Zhang, Li; Jiang, Zide; Chang, Changqing (Microbiology spectrum, 2023)
Sugarcane smut, caused by the basidiomycetous fungus Sporisorium scitamineum, is a global fungal disease resulting in substantial economic losses. Our previous research has highlighted the significant role of reactive oxide species (ROS) in the sexual reproduction of S. scitamineum , yet the underlying mechanisms remain unclear. In this study, we identified the cytochrome c -peroxidase encoding gene, Ss CCP1 , as crucial for oxidative stress resistance. We further found that absence of SsCcp1 leads to defects in mating/filamentation and disrupts intracellular ROS homeostasis. However, restoration of mating/filamentation of SsCCP1 deletion mutants was partially achieved with exogenous antioxidants (vitamin C or vitamin E). Notably, transcription of the pheromone response factor SsPRF1 , pivotal for mating/filamentation of S. scitamineum , is significantly reduced in the Ss CCP1 deletion mutants or under exogenous hydrogen peroxide (H 2 O 2 ) conditions. Nevertheless, the addition of exogenous vitamin C for 60 min significantly up-regulated the SsPRF1 gene in the Ss CCP1 deletion mutants. Moreover, the constitutive expression of SsPRF1 essentially reinstated the mating/filamentation of Ss CCP1 deletion mutants, suggesting that SsCcp1 mediates the transcriptional activity of SsPRF1 by maintaining ROS homeostasis to regulate the mating/filamentation of S. scitamineum . Further investigations revealed that SsCcp1 is necessary for ROS detoxification and full pathogenicity in planta . Overall, this study not only unveils the importance of SsCcp1 in S. scitamineum mating/filamentation, ROS detoxification, and virulence but also provides insights into the role of SsCcp1-regulated ROS homeostasis in sexual reproduction of S. scitamineum . Reactive oxygen species play an important role in pathogen-plant interactions. In fungi, cytochrome c -peroxidase maintains intracellular ROS homeostasis by utilizing H 2 O 2 as an electron acceptor to oxidize ferrocytochrome c , thereby contributing to disease pathogenesis. In this study, our investigation reveals that the cytochrome c -peroxidase encoding gene, SsCCP1 , not only plays a key role in resisting H 2 O 2 toxicity but is also essential for the mating/filamentation and pathogenicity of S. scitamineum . We further uncover that SsCcp1 mediates the expression of SsPrf1 by maintaining intracellular ROS homeostasis to regulate S. scitamineum mating/filamentation. Our findings provide novel insights into how cytochrome c -peroxidase regulates sexual reproduction in phytopathogenic fungi, presenting a theoretical foundation for designing new disease control strategies.